Pelatihan Penyusunan Standar Operasional Prosedur (SOP) Pelayanan Admnistrasi Pemerintahan Desa di Desa Sandang Pangan Kecamatan Sampolawa Kabupaten Buton Selatan - Junaid Gazalin (ADPERTISI, 2022)
Prioritizing maximum service demands that the quality of village government services is also considered. There are no available guidelines for working so that the ability of village officials in village government is still lacking, it is hoped that with this training solution, village officials know the basic principles in carrying out government administrative tasks. The importance of mentoring training in the preparation of standard operating procedures (SOP) is expected to improve the quality of human resources for village officials in providing services to the community. In addition, it is able to make village officials understand the orderly administration in terms of accountability reports and increase the discipline of village officials at work. This activity uses a training method, Focus group discussion (FGD) with evidence of a module resulting from the training in the preparation of the SOP